Peranan Penyuluh Pertanian Terhadap Produktivitas Usahatani Padi Sawah di Kecamatan Kobalima Kabupaten Malaka - Umbu Joka; Beatrix Dahu; Werenfridus Taena (Jurnal Penelitian Pertanian Terapan, 2022)
Agricultural extension agents play an important role in increasing the intelligence and competence of farmers, especially for farmers in border areas. This study aims to determine: 1). General depiction of rice farming and productivity; 2). The role of agricultural extension agents on rice farming productivity; 3). The role of agricultural extension agents on rice farming productivity through the behavior of farmers in Kobalima District, Malaka Regency. The sample of extension workers by census was 9 extension workers, while the farmer groups by purposive sampling were 9 farmer groups. Data analysis used descriptive analysis and path analysis. The results showed that the general description of rice farming and productivity of rice in Kobalima Subdistrict, covers a land area of 9.1 ha, production 31 tonnes and productivity 2.74 tonnes / ha. Directly, the role of agricultural extension agents affects the productivity of rice farming with a significant value of 0.004, with a coefficient of determination (R2) of 0.9. Meanwhile, the partial test of education, dissemination, facilitation, consultation, supervision has a significant effect on the productivity of rice farming. Indirectly, the role of agricultural extension agents has a significant effect on the productivity of rice farming through the behavior of farmers with a significant value of 0.053. The coefficient of determination (R2) is 0.999. While the partial test; facilitation has a significant effect on the productivity of lowland rice farming through the behavior of farmers in Kobalima District, Malaka Regency.